Planned Realignment Osteotomies Ahead of Knee Arthroplasty for Pronounced Joint Malalignment: A Case Report in Hereditary Multiple Exostoses Disease - Tim Schmid, MD; Marietta Schmid, MD; Pascal A. Schai, MD (Arthroplasty Today)
Various approaches have been reported to achieve correctly aligned total knee arthroplasty in cases of knee arthritis with pronounced extra-articular bone malalignment. Revision instrumentation and implants have enabled bone correction coincident with knee arthroplasty in notable tibial and/or femoral deviation, however increasing operative complexity and inherent risks. In the presented patient with hereditary multiple exostoses disease and progressing knee arthritis for extra-articular malalignment, elected treatment strategy was to primarily correct joint plane deformity through femoral and tibial osteotomies, ahead of and preparing for later knee arthroplasty. Staged osteotomies prior to total knee arthroplasty are effective for managing severe extra-articular malalignment, improving surgical outcome and prosthetic longevity.